Energy efficiency of electric motor-car rolling stock for suburban passenger transportation - Ivanov, Konstantyn (National Technical University "Kharkiv Polytechnic Institute", 2024)
The ways of research means to increase traction and energy indicators of electric motor-car rolling stock are analyzed. It has been determined that a significant improvement can be achieved with the use of energy recovery. The highest efficiency is achieved by accumulating energy in on-board storage devices.
Keywords: energy storage; energy efficiency; rolling stock; passenger transportation; energy recovery; storage devices